The effect of 8-week training program on physical and antropometric characteristics of teen male national boxing team - Kilic, Y.; Cinar, V. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2016)
To obtain a high level of performance, outstanding performance of nowadays athletes be characterized as complement of physiological, psychological and biomechanical factors. The aim of this study is exploration the effect of 8 weeks training program on certain physical and anthropometric values of 13-14 years male boxers. 24 boxers from Teen Male National Boxing Team Participating in the camp program realized in Kastamonu in 2011 are composed the research of study. 8 weeks training program determined by Boxing Federation applied to training group participated in the study. Weight, body fat percentage, body mass index, anthropometric measurements of biceps circumference, leg circumference, shoulder circumference, chest circumference, waist circumference are taken from the athletes at the start and end of the camp. It was applied Pre-test and post-test model. Independent t-tests implemented in data an alysis. SPSS 15.0 packaged software to Window was used in analysis and level of significance taken as p<0.05.It wasn?t find out any statistical discrepancy among the measurements worth weight of athletes forming the study group. But it is significant dis crepancy among the measurements in body fat rates (p<0,05).